Dampak Bullying Pada Siswa Sekolah Dasar: Kajian Literatur Sistematis - Arinata, Firdian Setiya; Mulawarman, Mulawarman; Mulyani, Petra Kristi; Awalya, Awalya; Wasono, Andy; Kurniawati, Erni; Mubarak, Muh Azhar (Jurnal Bimbingan dan Konseling Ar-Rahman, 2024)
This systematic review analyzes the impact of bullying on victims and perpetrators among elementary school students. This study used inclusion and exclusion criteria to filter relevant articles published between 2022 and 2024. Articles were obtained from two databases, Taylor & Francis and ScienceDirect, with the help of Boolean operators according to keywords. The study selection process followed the PRISMA method which involved four stages: identification, screening, eligibility, and inclusion. Of the total 6,527 articles identified, five articles met the inclusion criteria. Data synthesis was carried out qualitatively through thematic analysis. This review included five studies with a total sample of more than 97,000 participants from Spain, China, the United States, South Korea, and the Netherlands. The main results showed that bullying behavior significantly increased the risk of anxiety, depression, and suicidal ideation. In addition, bullies also experience long-term impacts, including behavioral and academic problems and the risk of criminality in adulthood. Limitations of this study include the use of a cross-sectional design, potential reporting bias, and lack of representation in cultural and long-term contexts. Future research should focus on longitudinal studies, more diverse instruments, and populations. These findings underscore the importance of comprehensive bullying prevention programs and targeted psychological interventions to address both the immediate and long-term impacts of bullying._____________________________________________________________Tinjauan sistematis ini menganalisis dampak bullying terhadap korban dan pelaku di kalangan siswa Sekolah Dasar. Penelitian ini menggunakan kriteria inklusi dan eksklusi untuk menyaring artikel relevan yang diterbitkan antara tahun 2022 hingga 2024. Artikel diperoleh dari dua data base, Taylor & Francis dan ScienceDirect, dengan bantuan operator Boolean sesuai kata kunci. Proses seleksi studi mengikuti metode PRISMA yang melibatkan empat tahap: identifikasi, penyaringan, kelayakan, dan inklusi. Dari total 6.527 artikel yang diidentifikasi, lima artikel memenuhi kriteria inklusi. Sintesis data dilakukan secara kualitatif melalui analisis tematik. Tinjauan ini mencakup lima studi dengan total sampel lebih dari 97.000 partisipan dari Spanyol, Tiongkok, Amerika Serikat, Korea Selatan, dan Belanda. Hasil utama menunjukkan bahwa perilaku bullying secara signifikan meningkatkan risiko kecemasan, depresi, dan ide bunuh diri. Selain itu, pelaku bullying juga mengalami dampak jangka panjang, termasuk masalah perilaku dan akademik serta risiko kriminalitas di usia dewasa. Keterbatasan penelitian ini mencakup penggunaan desain cross-sectional, potensi laporan yang bias, dan kurangnya representasi dalam konteks budaya serta jangka panjang. Penelitian di masa depan diharapkan berfokus pada studi longitudinal, instrumen dan populasi yang lebih beragam. Temuan ini menegaskan pentingnya program pencegahan bullying yang komprehensif dan intervensi psikologis yang terarah untuk mengatasi dampak langsung maupun jangka panjang dari bullying.